Corporate social responsibility disclosure in resource-based view and institutional theories context / Suzana San - San, Suzana (2011)
A corporate social responsibility (CSR) disclosure issues have been widely discussed in the past studies. However, there are still limited studies in Malaysia that examine the factors affecting CSR disclosure by the company using the combinations of Resource-Based View (RBV) and Institutional theories perspectives. This study provides an insight into the factors affecting CSR disclosure of the companies in the context of RBV and Institutional theories. By using CSR disclosure index of 150 Malaysian public listed companies in sensitive industries published in 2007 annual reports, this study examines the relationship of investment, chief executive officer (CEO) international experience, board interlocking and audit committee meeting with CSR disclosure. The findings show that there is a significant positive relationship between investment and CSR disclosure. However, there are insignificant relationship between CEO international experience, board interlocking and audit committee meeting with CSR disclosure. The finding indicates that one of the variables under RBV, that is investment influences CSR disclosure, however the CEO international experience does not affect CSR disclosure. Meanwhile, both of the variables under institutional theory which are board interlocking and audit committee meeting do not affect CSR disclosure.